Management of adolescent scoliosis: a comprehensive review of etiology and rehabilitation - Kuang, Hongwei; Chen, Luolan; Huang, Miao; Chen, Jianbin (Frontiers in Pediatrics, 2025)
Adolescent scoliosis (AS) is a complex spinal deformity characterized by a curvature exceeding 10 degrees, affecting 1%–3% of adolescents globally. Despite extensive research, its etiology remains multifactorial, involving genetic, biomechanical, neuromuscular, and environmental factors. This review synthesizes recent advances in understanding the pathogenesis of AS and explores the latest developments in non-surgical rehabilitation strategies, including physical therapy, bracing, exercise therapy, and psychological interventions. Emerging technologies, such as artificial intelligence, wearable devices, and virtual reality, are revolutionizing diagnostic accuracy and treatment personalization. The review also highlights the critical role of multidisciplinary collaboration and psychological support in improving patient outcomes. By identifying key research gaps and proposing innovative future directions—such as the integration of epigenetics, advanced biomechanical modeling, and AI-driven precision rehabilitation—this article aims to provide clinicians and researchers with a comprehensive framework for managing AS. Ultimately, this review underscores the importance of early detection, personalized treatment, and long-term follow-up in enhancing the quality of life for adolescents with scoliosis.